122 - THE PRODUCTION OF FREE RADICALS IN PHYSICAL ACTIVITY: A PHYSICAL EDUCATOR'S POINT OF VIEW (Fiep Bulletin - online, 2011)
The study aimed to discuss the production of free radicals in the body, the problems it can cause and the importance of antioxidants for health, based on data obtained from questionnaires given to physical activity supervisor teachers in the city of Teresina - Piauí. To support the study, a survey was carried out with 50 supervisors at 10 gyms in the city of Teresina-Piauí, to assess the level of knowledge about the formation and activity of free-radicals in the body and the action of antioxidants in the customary diet of people who exercise. The results showed that the supervisors generally have a moderately sufficient knowledge about free radicals. They do not have enough information about their action mechanisms in the body. Therefore it is evident that multidisciplinary training is needed with the aim of improving the efficiency of training to promote health and quality of life.
Keywords: free radicals; antioxidants; knowledge; health; quality of life